Turbidity and color removal from river water with tree xylem as a natural filter - Delikanlı, Niyazi Erdem (Pamukkale Univ, 2025)
This study evaluates the efficiency of xylem-based filters derived from five tree species-Pinus pinea, Populus nigra, Pinus brutia, Tilia tomentosa, and Quercus petraea-in removing turbidity and color from Bart & imath;n River water samples. Filtration experiments were conducted under varying pressure conditions (5 psi, 10 psi, and 15 psi) to assess the performance of each xylem filter based on flow rate, turbidity removal, and color reduction. The results highlighted that gymnosperm species, particularly Pinus pinea, exhibited high turbidity (up to 99.36%) and color removal efficiency (up to 95.58%) at lower pressures. Conversely, angiosperm species demonstrated higher flow rates but lower filtration efficiencies. Durability analysis of pit membranes revealed that high pressure could compromise their integrity, slightly reducing efficiency. These findings indicate that xylem-based filtration is a promising, costeffective, and eco-friendly water purification method suitable for areas lacking advanced water treatment systems. Further optimization of pressure conditions and enhanced pit membrane durability are recommended to maximize efficiency and longevity.
Keywords: Xylem filtration; Natural water purification; Sustainable water treatment; Eco-friendly filtration; Wood-Based filtration; Plant xylem